Irrigation effect of Dioscorea hispida Dennst. Aqueous Tuber Extract on Allelopathic Action of Maize and Mustard - Nashriyah, Mat; Mohd Hudzari, Haji Razali; Mohammad Moneruzzaman, Khandaker (2016)
Tuber of Dioscorea hispida (Ubi Gadong) from different frequency of water supplied (control: distilled water; T1:watering at one day interval; T2: watering at every day; T3: watering at two days Interval; T4:watering at five days interval; and TS: watering at six days Interval) were extracted and kept in aqueous formed for using as treatment/water supply to maize and mustard. Bioassay tests on maize and mustard seed have identified that Tl and T4 had the highest significant difference for maximum increment of radicle length at p valtie =0.004. These laboratory results had been supported by allelopathic effects that had been carded out in the field. Then, there was significant difference obtained through mustard and maize growth which was deductible for the treatment and control. Decisi11e test conducted In the field trial had explained that Tl an<i T4 had shown growth factor stimulation to maize and mustard plant, respectively. The differences of optimum allelopathic efforts of D. hispida might be due to the optimum concentration of allelochemicaJs produced in D. hispida tuber which triggered the highest radicle elongation of maize and mustard, respectively.